THE KILLER-SIMULACRA: When the Text Become Lethal Weapon: Study on The Politics of Simulacra on Basuki Tjahya Purnana (Ahok) (Ushuluddin International Conference (USICON), 2017)
This paper will elaborate how text transforming from ordinary to be lethal weapon on Basuki Tjahya Purnama